Circadian Rhythms of Urinary Cortisol Levels Vary Between Individuals in Wild Male Chimpanzees: A Reaction Norm Approach - Sonnweber, Ruth; Araya-Ajoy, Yimen G.; Behringer, Verena; Deschner, Tobias; Tkaczynski, Patrick; Fedurek, Pawel; Preis, Anna; Samuni, Liran; Zommers, Zinta; Gomes, Cristina; Zuberbühler, Klaus; Wittig, Roman M.; et al. (Frontiers in Ecology and Evolution, 2018)
Investigating the repeatability of trait variation between individuals, that is the amount of individual variation in relation to overall phenotypic variation, indicates an upper level of heritability and reveals whether a given trait may be subject to selection. Labile traits are characterized by high levels of flexibility and consequently low trait repeatability is expected. Indeed, research examining glucocorticoid levels in various non-mammal species found low repeatability scores. However, mammals may be different in this respect as (i) differential maternal care early in life has the potential to prime hypothalamic-pituitary-adrenal axis functioning and (ii) allelic variation affecting hypothalamic-pituitary-adrenal axis functioning has been reported. Individuals often differ from each other in average and/or plastic labile trait expression, two aspects that can be described using a reaction norm approach. Both consistent and flexible reaction norm expression has been argued to serve adaptive purposes, depending on the stability and predictability of environmental conditions. Here we investigated both trait and reaction norm repeatability of urinary cortisol levels in wild adult male chimpanzees. To capture the expression of the circadian urinary cortisol rhythm of individual males over time, urine samples were collected throughout the day. In total data of 30 males collected over a period of 8 years were included in the dataset. No male was sampled over the whole 8-year period however. We found minor levels of trait repeatability but considerable reaction norm repeatability. This implies a minor role of genetic or priming factors on cortisol excretion, but reveals that males differ consistently in average urinary cortisol levels and the shape of the circadian urinary cortisol rhythm. Relating these results to fitness parameters will provide answers to questions on the adaptive value of reaction norm repeatability of this labile hormonal trait in the future.